Causal associations between gut microbiota and primary biliary cholangitis: a bidirectional two-sample Mendelian randomization study - Zhang, Jiahao; Wu, Gefeng; Tang, Yuhong; Liu, Huanxiang; Ge, Xinyu; Peng, Rui; Cao, Jun; Tu, Daoyuan; Su, Bingbing; Jin, Shengjie; Jiang, Guoqing; Zhang, Chi; et al. (Frontiers in Microbiology, 2023)
Previous studies have suggested an association between gut microbiota and primary biliary cholangitis (PBC). Nonetheless, the causal relationship between gut microbiota and PBC risk remains unclear.A bidirectional two-sample Mendelian Randomization (MR) study was employed using summary statistical data for gut microbiota and PBC from the MiBioGen consortium and Genome-Wide Association Studies (GWAS) database to investigate causal relationships between 211 gut microbiota and PBC risk. Inverse variance weighted (IVW) method was the primary analytical approach to assess causality, and the pleiotropy and heterogeneity tests were employed to verify the robustness of the findings. Additionally, we performed reverse MR analyses to investigate the possibility of the reverse causal association.The IVW method identified five gut microbiota that demonstrated associations with the risk of PBC. Order Selenomonadales (odds ratio [OR] 2.13, 95% confidence interval [CI] 1.10-4.14, P = 0.03), Order Bifidobacteriales (OR 1.58, 95% CI 1.07-2.33, P = 0.02), and Genus Lachnospiraceae_UCG_004 (OR 1.64, 95%CI 1.06-2.55, P = 0.03) were correlated with a higher risk of PBC, while Family Peptostreptococcaceae (OR 0.65, 95%CI 0.43-0.98, P = 0.04) and Family Ruminococcaceae (OR 0.33, 95%CI 0.15-0.72, P = 0.01) had a protective effect on PBC. The reverse MR analysis demonstrated no statistically significant relationship between PBC and these five specific gut microbial taxa.This study revealed that there was a causal relationship between specific gut microbiota taxa and PBC, which may provide novel perspectives and a theoretical basis for the clinical prevention, diagnosis, and treatment of PBC.